2005
DOI: 10.1029/2004ja010949
|View full text |Cite
|
Sign up to set email alerts
|

High‐latitude Joule heating response to IMF inputs

Abstract: [1] We evaluate the response of the high-latitude Joule heating to orientation and magnitude of the interplanetary magnetic field (IMF). Approximately 9000 individual Joule heating patterns derived from data assimilation for the northern hemisphere were used to develop averaged and hemispherically integrated Joule power maps for the northern hemisphere north of 40°magnetic latitude. Hemispherically integrated Joule heating increases with IMF magnitude when the IMF is southward, but is relatively unchanged with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
51
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 29 publications
12
51
0
Order By: Relevance
“…The widely accepted paradigm is documented in papers by Weimer (2005), Cosgrove et al (2014), McHarg et al (2005, and others, in which the auroral zones and cusp dominate highlatitude energy input. The main reason for the discrepancy between our results and previous work lies in the way the data have been treated.…”
Section: Discussionmentioning
confidence: 99%
“…The widely accepted paradigm is documented in papers by Weimer (2005), Cosgrove et al (2014), McHarg et al (2005, and others, in which the auroral zones and cusp dominate highlatitude energy input. The main reason for the discrepancy between our results and previous work lies in the way the data have been treated.…”
Section: Discussionmentioning
confidence: 99%
“…Tsurutani et al (2006b) proposed that HILD-CAA events cause high-latitude heating and corresponding disturbance dynamo effects which in turn affect high-latitude VTEC intensities. High-latitude thermospheric heating in response to different polarity of IMF Bz has been extensively studied by McHarg et al (2005). They concluded that hemispherically integrated Joule heating increases dramatically in the post-midnight sector of the auroral zone during southward IMF intervals.…”
Section: Discussionmentioning
confidence: 99%
“…With moderately southward IMF, the total ionospheric heating in both hemispheres is several hundred gigawatts (GW) [Chun et al, 1999[Chun et al, , 2002McHarg et al, 2005], and during major geomagnetic storm periods the heating may exceed 1000 GW [Lu et al, 1998]. The result is that the thermosphere expands upward, creating additional drag on objects in low Earth orbit (LEO).…”
Section: Introductionmentioning
confidence: 99%